2022
DOI: 10.31234/osf.io/3xjcf
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Robust holistic face processing in early childhood during the COVID-19 pandemic

Abstract: The timing of the developmental emergence of holistic face processing and the role that experience plays in it are somewhat controversial topics. Using an online testing platform, we investigated holistic face perception in 4-6-year-old children with a two-alternative forced-choice task in which they saw pairs of composite faces and had to decide whether the faces were the same or different. We also assessed children’s exposure to masked faces during the COVID-19 pandemic with a parental questionnaire to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…With respect to preferences for transparent face shields over surgical masks, children's preferences are not aligned with their parents' views: children have an equal preference for others with transparent face shields and surgical masks, reporting neither as more frightening than the other (Forgie et al., 2009). In addition, the limited research conducted thus far has shown that emotional signaling (Ruba & Pollak, 2020), language comprehension (Singh et al., 2021), and face processing (Yates & Lewkowicz, 2022) remain robust when the lower part of the face is covered by surgical masks. Importantly, there is evidence that children may even be more resilient to masked communication than adults.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to preferences for transparent face shields over surgical masks, children's preferences are not aligned with their parents' views: children have an equal preference for others with transparent face shields and surgical masks, reporting neither as more frightening than the other (Forgie et al., 2009). In addition, the limited research conducted thus far has shown that emotional signaling (Ruba & Pollak, 2020), language comprehension (Singh et al., 2021), and face processing (Yates & Lewkowicz, 2022) remain robust when the lower part of the face is covered by surgical masks. Importantly, there is evidence that children may even be more resilient to masked communication than adults.…”
Section: Discussionmentioning
confidence: 99%